1993
DOI: 10.3171/jns.1993.78.3.0375
|View full text |Cite
|
Sign up to set email alerts
|

Improving the outcome of severe head injury with the oxygen radical scavenger polyethylene glycol-conjugated superoxide dismutase: a Phase II trial

Abstract: Formation of the oxygen radical superoxide anion is one of the final events of several metabolic pathways in the cascade that leads to delayed neuronal death after traumatic or ischemic brain injury. In the laboratory, scavenging of the superoxide anion with native superoxide dismutase (SOD) or polyethylene glycol (PEG)-conjugated SOD (PEG-SOD) has been shown to be beneficial in several types of traumatic and ischemic injury. Accordingly, PEG-SOD was utilized in a randomized controlled Phase II trial to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(83 citation statements)
references
References 39 publications
0
82
0
1
Order By: Relevance
“…21 Recently, a trial with SOD in humans with severe head injuries showed that death and vegetative state were increased in patients receiving a placebo compared with those receiving polyethylene glycol and SOD. 22 Intracellular generation of superoxide or other species could alter structures and/or production of nucleotides, second messengers, receptors, and membranes, and the movement of superoxide out of the cell through anion channels could result in high concentrations of activated oxygen species at cell surfaces, including endothelium. Such oxygen species are thought to antagonize NO function and to contribute to altered cerebral hemodynamics after FPI in the piglet because free radical scavengers partially restored decreased CSF cGMP concentration and decreased responses to NO-dependent dilator stimuli such as opioids.…”
Section: Discussionmentioning
confidence: 99%
“…21 Recently, a trial with SOD in humans with severe head injuries showed that death and vegetative state were increased in patients receiving a placebo compared with those receiving polyethylene glycol and SOD. 22 Intracellular generation of superoxide or other species could alter structures and/or production of nucleotides, second messengers, receptors, and membranes, and the movement of superoxide out of the cell through anion channels could result in high concentrations of activated oxygen species at cell surfaces, including endothelium. Such oxygen species are thought to antagonize NO function and to contribute to altered cerebral hemodynamics after FPI in the piglet because free radical scavengers partially restored decreased CSF cGMP concentration and decreased responses to NO-dependent dilator stimuli such as opioids.…”
Section: Discussionmentioning
confidence: 99%
“…A phase II clinical trial in which PEG-SOD was administered intravenously to adults within twelve hours after severe head injury demonstrated an improvement in three-and six-month mortality and functional outcome (as measured by the Glasgow Outcome Scale) in patients receiving the highest dose of PEG-SOD (10,000U/kg). 112 However, when further tested in a phase III randomized controlled trial, no statistical difference in mortality or outcome at three months post-injury was found between controls and patients receiving either 10,000U/kg or 20,000U/kg of PEG-SOD. 113 The free radical scavenger tirilazad mesylate also failed to show any benefit over placebo in a randomized controlled trial of adults with severe and moderate TBI with the exception of males presenting with a subarachnoid hemorrhage.…”
Section: Oxidative Damagementioning
confidence: 99%
“…production in the pathogenesis and evolution of acute brain injury has not been resolved. Numerous studies have investigated the therapeutic efficacy of antioxidant compounds in both animal models and humans (Forsman et al, 1988;Matsumiya et al, 1991;Uyama et al, 1992;Muizelaar et al, 1993). Results have been mixed, and issues of bioavailability of the various compounds have not been resolved (Haun et al, 1991).…”
mentioning
confidence: 99%